THE ROLE OF MIDWIVES IN RECOGNIZING SIGNS AND SYMPTOMS OF POSTPARTUM DEPRESSION - Hotma Ulina Sagala (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2023)
Background: Postpartum depression is a problem that occurs postpartum, affects up to 20% of women, and can adversely affect both mother and child. Postpartum depression is a feeling disorder experienced by mothers 2 weeks after giving birth to 3 months or more, this condition is a continuation of the baby blues. Women with postpartum depression are not easily identifiable and can display a variety of signs and symptoms. Early symptoms are not easy to determine, usually, patients have shown signs before entering the postpartum period. In cases of postpartum depression, it is often known too late by the family and in this case, the midwife acts as a provider of routine care from antenatal care to postpartum services or visits.Objective: To investigate the role of midwives and professionals in health care providers in recognizing the signs and symptoms of perinatal depression.Method: This paper involved on referral sources and based on observation by author.Results: Midwives have an important role to detect signs and symptoms of mental health disorders in their practice but are hindered by organizational and practitioner-related barriers. With training and organizational support, midwives can develop skills and knowledge needed for early detection, provide mental health care.Conclusion: Midwives need to increase awareness of early detection, early referral system and prompt education to help patient withpostpartum depression get better prognosis and outcomes. Keywords: midwives, postpartum, depression.